Новая система постулатов в познании материи. I - Вышинский, В.А. (Управляющие системы и машины, 2015)
Предложена система постулатов – аксиом физики по Д. Гильберту. Несмотря на ее несамодостаточность в естествознании, можно построить модель существования материи, в которой известные постулаты современной физики: масса, инерция, поле, гравитация и другие свойства вещества приобретают смысл лемм и теорем новой системы постулатов. Это существенно упрощает физическое понимание свойств вещества. Запропоновано систему постулатів – аксіом фізики за Д. Гільбертом. Незважаючи на її несамодостатність в природознавстві, можна побудувати модель існування матерії, в якій відомі постулати сучасної фізики: маса, інерція, поле, гравітація та інші властивості речовин. The solution of the sixth Hilbert's problem indicates the impossibility «to add together mathematically the system of physics axioms». However, it isn't an insurmountable barrier in the natural researches. It is possible to build the system of postulates (axioms) which don't satisfy the self-sufficiency, i.e. on its basis it is impossible to learn the various properties of a matter, and at the same time, in this system the known postulates, on which the modern physics is based, have the character of lemmas, theorems and tasks. This new system feature allows successful learning of those substance properties that in modern physics is a subject of its research. Such system of the postulates, confirmed by the experiment practice is offered. Each of them reflects the known law of the nature. In the case under consideration, as laws are chosen those, which are general not only for a material form of the matter existence, but also for its other forms, and in particular for vacuum. Among the laws taken as postulates, it is necessary to pay attention to the law that the matter in nature is in the determined look. It means that the researching approach denies the fortuity of the phenomena, which is inherent in the nature existence. On the basis of the law of unity and conflict of opposite, the new judgment is implemented into the offered system that the matter in the nature can't exist alone. In contrast to the material substance we also consider the substance of the empty space. The special attention is paid to such phenomenon as development. It is shown that it is inherent only in the material systems which are in «conflict» with the well-known principium’s of thermodynamics. We point out that because of this the usual physical (not cybernetic) systems aren't able to develop. The system of postulates includes the properties of the law of the nature according to which the matter exists in the repeating forms. Due to this law, the endless sequence of the researches concerning the nature perception can be organized, avoiding the impossibility of the postulates creation, which satisfy the self-sufficiency. The system with more than 10 postulates is offered. There is inexact number of postulates quantity because the system is open, i.e. in the future it is possible to add the new postulates (laws of the nature) to its list.